American evangelicals : a contemporary history of a mainstream religious movement - Hankins, Barry, 1956- (Critical issues in history., 2008)
There may be no group in American society that is more talked about but so little understood as Evangelical Christians. Sometimes dismissed as violent fundamentalists and ignorant flat earthers, few can doubt the political, cultural, and religious significance of the Evangelicals. Barry Hankins puts the Evangelical movement in historical perspective, reaching back to its roots in the Great Awakening of the 18th century and leading up to the formative moments of contemporary conservative Protestantism. Taking on key topics such as the standing of science, the authority of scripture, and gender.